2014
DOI: 10.3807/josk.2014.18.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Micrometer-Sized Spectrometer by Using Plasmonic Tapered Channel-Waveguide

Abstract: It has been a critical issue to reduce the size of spectrometers in many fields such as on-chip chemical and biological sensing. The proposed plasmonic channel-waveguide with a sub-micrometer width has a cutoff frequency which enables us to control wavelength dependent propagation properties. We focused on the capability of the waveguide for spectral-to-spatial mapping when the waveguide width changes gradually. In this paper, we propose a plasmonic tapered channel-waveguide structure as a compact spectrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A plasmonic channel waveguide is a groove-type waveguide with a rectangular cross-section through which surface plasmon polaritons (SPPs) propagate. Recent studies have reported several applications of the plasmonic channel waveguide with a cut-off frequency for optical lasing [ 17 , 18 ], index sensing [ 4 , 8 ] and spectrometers [ 19 ]. The cut-off of the SPPs occur in the rectangular grooved channel waveguide with a finite width of the bottom, which is due to confinement of the metallic sidewalls.…”
Section: Introductionmentioning
confidence: 99%
“…A plasmonic channel waveguide is a groove-type waveguide with a rectangular cross-section through which surface plasmon polaritons (SPPs) propagate. Recent studies have reported several applications of the plasmonic channel waveguide with a cut-off frequency for optical lasing [ 17 , 18 ], index sensing [ 4 , 8 ] and spectrometers [ 19 ]. The cut-off of the SPPs occur in the rectangular grooved channel waveguide with a finite width of the bottom, which is due to confinement of the metallic sidewalls.…”
Section: Introductionmentioning
confidence: 99%
“…Such a strong enhancement of the E-field in a small volume is highly advantageous not only for many diverse applications such as sensors 10 11 12 13 , lasers 14 15 16 17 , and color displays 18 19 20 21 but also for fundamental control of optical phenomena 22 23 . Consequently, such gap structures, also called metal-insulator-metal (MIM) structures 24 or gap plasmons 25 , have been the subject of intense research activities 26 27 28 29 30 31 32 33 34 35 .…”
mentioning
confidence: 99%